Frequency Scaling from 19 to 39 GHz Using Alphasat Data from Prague - Pek, Viktor; Fišer, Ondřej; Pitaš, Karel (IEEE (Institute of Electrical and Electronics Engineers), 2019)
In this contribution we construct scatterplots 39 vs. 19 GHz of total attenuation (pairs) on satellite link. The results from the satellite link satellite Alphasat - two beacon receivers at the Institute of Atmospheric Physics (IAP) in Prague (Czech Republic) are used to investigate the frequency scaling. The usually used frequency scaling formulas are tested through our measured attenuation A pairs A(39) -A(19) GHz (one minute values on one hand and peak values on the other hand). The power law scaling method (power of frequency ratio n=1.4) seems to be most appropriate in our case. However, the ITU-R method could be also recommended as a general method which brings sufficient results.
Frekvenční škálování od 19 do 39 GHz pomocí dat Alphasat z Prahy
Keywords: frequency scaling; satellite link; radiowave propagation; škálování frekvence, satelitní spojení, šíření rádiových vln